(untitled) (Biological Sciences - PJSIR, 2023)
Starch hydrolyzing enzymes breaks the complex structures of starch are naturally synthesized by animals, plants and micro-organisms. These have several industrial applications like fuel production, textile industry, bread and baking, detergents, food, paper and pharmaceutical industry. The animal and poultry feed contains starch components. The digestibility of starch food in animals and birds can be increased by the addition of amylase producing micro-organisms in feed. Microbial sources gained importance over others by better quality, cost effective production and easy genetic manipulations. Bacillus and Aspergillus species are among major sources of amylases. However, enzymes market is always deficient to meet industrial demands. So, the search for new sources and improvement of enzyme stability under extreme conditions is priority. Growth optimization under different physical and chemical factors, mutagenesis and genetic modifications of microbial cells are different ways for enhanced production of amylases to meet demands of starch based industries.